Genetic engineering and gene manipulation: the right (of future generations) to surprise - Chorianopoulou, Maria K. (Ηθική. Περιοδικό φιλοσοφίας, 2021)
Genetic engineering is currently at the forefront of biotechnological innovation and aspires to change once and for ever the way we understand and handle human nature. Especially the growth of Eugenics makes us visualise a different world, where humanity will not only dispense itself from the detrimental gene mutations that are accountable for fatal illnesses, but will also ameliorate through prenatal gene manipulation. In the first part of this paper, I will introduce the responsibility-oriented morality of Hans Jonas, who supports vividly all efforts of negative Eugenics but seems sceptical about genetic enhancement, since on the one hand we have no right to decide on behalf of our descendants on what is best for them, and on the other due to his view that the abundance of our genetic stock should not hang on parents’ desires. In the second part, I will correlate these oppositions with Hannah Arendt’s concept of “natality”. Not only do Jonas and Habermas invoke it with applause; “natality” also discloses the very essence of birth, namely that each newborn epitomises total unpredictability and promises to renew human affairs. So, gene manipulation for enhancement purposes seems to encroach on “natality’s” dominion and diminish future autonomy. Finally, I will argue that, if Arendt’s conceptual frame consolidates objections to positive Eugenics, each unborn child holds a right to surprise, the content of which is not limited to an individual level but touches society and humanity.